Obstacles for MSMEs (Culinary, Fashion, Tour & Travel) in Implementing Digital Transformation - Al Aksar, Natiq; Ratnani, Mariana Ratih (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2025)
This study examines the inhibiting factors of digital transformation in MSMEs by integrating perspectives from Adaptive Structuration Theory and Dynamic Capabilities Theory. Digital transformation in this research is defined as the adoption of advanced technologies such as mobile platforms, artificial intelligence, cloud computing, blockchain, and IoT to enhance customer experience, optimize operational processes, and develop innovative business models. The research is motivated by the significant impact of the pandemic crisis on MSMEs in Indonesia. The inhibiting factors in Adaptive Structuration Theory were developed based on a synthesis of findings from DeSanctis & Poole and Wiesböck & Hess, while aspects of Dynamic Capabilities Theory were adapted from Eisenhardt & Martin and Warner & Wager. The research method utilized an online survey via Google Forms targeting MSME owners and managers in the culinary, fashion, and travel sectors, with 206 valid respondents out of 247 collected questionnaires. Data analysis employed Structural Equation Modeling-Partial Least Square (SEM-PLS) using Smart PLS 3.0 software. The findings reveal that digital transformation barriers significantly negatively affect digital implementation, while digital transformation itself positively impacts business performance. These results reinforce the relevance of both theories as conceptual frameworks for analyzing digitalization challenges while providing practical recommendations for MSMEs to accelerate digital technology adoption as a survival strategy during crises, particularly the COVID-19 pandemic. The study also highlights the importance of digital-based business strategy updates to enhance business resilience.